Evaluasi Kinerja Pembangunan Program Kerja Base Transceiver Station (BTS) Menggunakan Logical Framework Analysis Studi Pada Badan Aksesibilitas Telekomunikasi dan Informasi (BAKTI) KOMINFO - Indah Dwi Chyntia Riswandi; Suprapto Suprapto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The population of Indonesia is mostly spread in areas that have not been reached by telecommunications infrastructure. Indonesia's geographical conditions are very diverse, causing infrastructure development to not be carried out optimally. BAKTI is an Indonesian government company that provides ICT services that can be enjoyed by all levels of Indonesian society. BAKTI, especially at the Infrastructure Directorate, created a BTS work program that took place in the Telecommunications Service Blankspot area. The construction of BTS is a real effort by the government to overcome telecommunication gaps felt by the community. This study aims to determine the results of the performance evaluation of the BTS work program using the LFA (Logical Framework Analysis) method, which is useful both in planning, monitoring and management evaluating the development of a work program. LFA consists of seven stages of analysis, that is stakeholder analysis, problem analysis, objective analysis, strategy analysis, log frame (project plan), activity planning, and resources. In the LFA stage, SWOT analysis is conducted to find out how the organization acts in overcoming the problem. The results of this study found that the BTS work program was quite maximal, because the evaluation results showed that there was conformity with the main objectives set by BAKTI. Recommendations are made at each stage of the LFA, so that the recommendations are more specific and can improve performance, and are made based on system information management theories.